The Role of Financial Literacy on Financial Behavior - Pipit Rosita Andarsari; Mega Noerman Ningtyas (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2019)
A number of previous empirical studies found that, financially speaking, literate people tends to do budgeting, saving, controlling expenses, managing debt well, participating in stock market and planning pension fund, etc. In other words, the higher an individual’s knowledge and understanding of financial concept, the more likely they are to behave financially well in their daily life. Financial literacy is needed by everyone, including womenpreneur because not only they have to be able to manage their personal finance, they should also manage their business finance. Financially literate people are more likely to get access to external funding and to develop their business. This research aims to examine the role played by financial literacy on financial behavior of womenpreneur in Malang. Financial literacy was measured using 11 questions modified from Lusardi & Mitchell (2011) and financial behavior was measured using 8 questions taken from INFE. The sample was 95 respondents who were female (owners of) Micro, Small and Medium Enterprises in Malang. The data were collected using questionnaire. We used Partial Least Square with Smart PLS 3 to examine the variables. After the first bootstrapping process, we drop some invalid indicators and then perform the second bootstrapping. The result showed that all of the remaining indicators were valid and financial literacy had been found to have positive significant (influence) on financial behavior.